2018
DOI: 10.1002/ejp.1341
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐hypersensitive effect of angiotensin (1‐7) on streptozotocin‐induced diabetic neuropathic pain in mice

Abstract: Background We have recently reported that the spinal angiotensin (Ang) converting enzyme (ACE)/Ang II/AT1 receptor axis and downstream p38 MAPK phosphorylation are activated in streptozotocin (STZ)‐induced diabetic mice and lead to tactile hypersensitivity. Moreover, our previous results suggested that the intrathecal (i.t.) administration of Ang (1‐7), an N‐terminal fragment of Ang II, may attenuate the Ang II‐induced nociceptive behaviour through the inhibition of p38 MAPK phosphorylation via Mas receptors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Moreover, a recent study showed that SARS-CoV-2 can enter the human body via ACE2 receptors on the surface of human cells and cause disease [5] . It is intriguing that ACE2 receptors are also expressed on the membrane of spinal cord neurons [9,10] , further suggesting that SARS-CoV-2 is implicated in acute myelitis based on the specific ACE2 receptors on the surface of spinal cord neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent study showed that SARS-CoV-2 can enter the human body via ACE2 receptors on the surface of human cells and cause disease [5] . It is intriguing that ACE2 receptors are also expressed on the membrane of spinal cord neurons [9,10] , further suggesting that SARS-CoV-2 is implicated in acute myelitis based on the specific ACE2 receptors on the surface of spinal cord neurons.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 receptors are also expressed on the surface of spinal cord cells [9,10] . Whether spinal cord neurons are implicated in COVID-19 remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This theory is the result of prior research on SARS-CoV [10]. ACE2 receptors are also expressed on the surface of spinal cord cells [11,12]. Accordingly, it is comprehensible that COVID-19 also involves the spinal cord.…”
Section: Discussionmentioning
confidence: 86%
“…The presence of ACE2 receptors on the surface of spinal cord neurons supports the cause of acute myelitis as a post inflectional neurological complication [35,36]. Studies in children with COVID-19 have shown that GM-CSF levels were significantly higher in the cerebrospinal fluid (CSF) in SARS-CoV2 patients with CNS impairments than in the serum sample of SARS-CoV2 patients with classical respiratory illness [39].Cases of SARS-CoV causing encephalitis in patients and the large homologue sequences it shares with SARS-CoV2 makes it likely that new strain can also pose a threat to the CNS.…”
Section: -Ace-2 Receptor Expression and Neuro-tropism Of Sars-cov2mentioning
confidence: 89%